2017
DOI: 10.3892/etm.2017.4919
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane may be more beneficial than propofol in patients receiving endoscopic variceal ligation and endoscopic variceal sclerotherapy: A randomized, double-blind study

Abstract: Abstract. The aim of the present study was to evaluate the safety and efficacy of various general anesthesia regimens during endoscopic variceal ligation (EVL) and endoscopic variceal sclerotherapy (EVS). A total of 123 patients with American Society of Anesthesiologists physical status III and IV, aged 40-70 years, undergoing general anesthesia for EVL and EVS were randomly divided into two groups: Sevoflurane anesthesia (group S; n=60) and propofol anesthesia (group P; n=60). Vital signs, particularly heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
1
10
0
1
Order By: Relevance
“…Furthermore, compared with sevoflurane, propofol is metabolized dependent of liver and renal function; therefore, it is less controllable. Tang et al reported that patients receiving propofol-based intravenous anesthesia experienced a delay in the decided extubation time compared with the sevoflurane group (19), which is in accordance with our results. In contrast, of all currently used anesthetics, the pharmacokinetic properties of sevoflurane come closest to that of the ideal anesthetic.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, compared with sevoflurane, propofol is metabolized dependent of liver and renal function; therefore, it is less controllable. Tang et al reported that patients receiving propofol-based intravenous anesthesia experienced a delay in the decided extubation time compared with the sevoflurane group (19), which is in accordance with our results. In contrast, of all currently used anesthetics, the pharmacokinetic properties of sevoflurane come closest to that of the ideal anesthetic.…”
Section: Discussionsupporting
confidence: 93%
“…It was found that patients' sedation score in group A was lower than that in group B, and the incidence of pain in group A was higher than that in group B, indicating that patients had a high acceptance of propofol combined with sevoflurane anesthesia and a low incidence of adverse reactions. Cancer patients were prone to restlessness and other adverse reactions in general anesthesia due to pain, so sedation and analgesia effect were the main indicators to evaluate the anesthetic effect (21,26). In addition to produce general anesthesia, sevoflurane also had vasodilator and analgesic effects, so it is more suitable for elderly patients and patients with cardiovascular insufficiency (27).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years the inhalational anesthetic sevoflurane has replaced other volatile anesthetics due to its quick induction, stable maintenance, rapid revival and because the irritation it causes is mild [1]. However, recent evidence has shown that sevoflurane can lead to pathophysiological alterations of the brain during the recovery period, such as neuronal apoptosis, tau aggresomes, abnormal discharge of neurons, and neuroinflammation, which cause neurodegenerative changes in the development of the mammalian brain [26].…”
Section: Introductionmentioning
confidence: 99%